Feasibility study : setting up a private institution with a boarding school concept. - Wee, Laverne. (2008)
The purpose of the project is to find out whether a boarding school concept (where teachers and children stay together 24 hours a day) will work in Singapore. One main selling point of our school will also be our curriculum. We are going to adopt Gardner's eight intelligences into our school system, apart from what other schools, both government and private have offered. Research will include whether the parents and the teachers will like this new idea or not anf to forecast the demand for our school.